2020
DOI: 10.3390/ijerph17061859
|View full text |Cite
|
Sign up to set email alerts
|

A “Forbidden Fruit Effect”: An Eye-Tracking Study on Children’s Visual Attention to Food Marketing

Abstract: Obesity in children is an international health concern. Against this background, there is an increasing interest in understanding how healthy and unhealthy food marketing in narrative media can affect children. In particular, children’s implicit reactions, such as visual attention and emotional arousal, are far from being sufficiently understood. We conducted an eye-tracking study, presenting children one of two versions of a narrative media-stimulus, either presenting an unhealthy food (i.e., candy condition;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…However, no significant difference was observed in the children's visual attention or emotional arousal towards candy or food conditions. There is a significant difference in children's emotional arousal to unhealthy products due to the parent's restriction of candy at home [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, no significant difference was observed in the children's visual attention or emotional arousal towards candy or food conditions. There is a significant difference in children's emotional arousal to unhealthy products due to the parent's restriction of candy at home [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although the studies reported in this survey showed a significant difference and the hypothesis generated was accepted, some limitations still exist. The common limitations identified in the studies are short period of time for implementation [ 53 ], smaller sample size [ 27 , 37 ], nongeneralizability [ 25 , 27 , 32 , 39 , 53 ], nonrandomization trials [ 52 ], and no control group and post only group [ 45 ]. Few other studies have reported the possibility of cross-contamination among the control and experimental group [ 33 ], increased dropout of participants before completing the post-test questionnaire [ 52 ], and underestimation of participant's knowledge of expressing words which might directly affect the animation [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The forbidden-fruit effect means that the more ethical an organization becomes, the more attractive unethical behavior becomes until it could not be resisted. This second effect of the downward force is captured by the expression, “Good makes bad more attractive.” The forbidden-fruit effect is present in the literature (e.g., Binder et al, 2020 ; Fitzgibbon et al, 2020 ). The name of the effect refers to the biblical story of the forbidden-fruit in paradise that became too tempting and the consumption of which had momentous consequences.…”
Section: The Downward Forcementioning
confidence: 92%
“…Considering the source-related effects, studies suggest that majority cues [ 98 ] and what a media character represents are crucial. For instance, peer-led marketing, as opposed to influencer- or celebrity-led marketing, is suggested to be a stronger predictor of consumers’ eating behavior [ 99 ] and decisions to consume healthier foods [ 96 ].…”
Section: Promoting Fandv Among Childrenmentioning
confidence: 99%